PERBANDINGAN ANTARA RETURN ON ASSETS (ROA) DENGAN ECONOMIC VALUE ADDED (EVA) DALAM MENILAI KINERJA PERUSAHAAN (Studi pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia) - Wawo, Andi Basru; Nurdin, Emillia; Saraswati, Febby Annisa (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
This study aimed to compare the financial performance of pharmaceutical companies listed on the Indonesian Stock Exchange by using ROA and EVA. The population in this study is a pharmaceutical company listed on the Indonesia Stock Exchange. A total of five samples were obtained by using purposive sampling. In analyzing the data used is descriptive analysis method.From the calculation of Return on Assets (ROA) shows that five pharmaceutical companies listed on the exchange effect of Indonesia average ROA is positive, while the calculation of Economic Value Added (EVA) shows that five pharmaceutical companies listed on the exchange effect of Indonesia average EVA is positive. The research is based on the calculation of Economic Value Added (EVA) can already be used in the assessment of performance company particularly in assessing the interests of shareholders.Â Keyword: return on assets, economic value added, performance company